Geochemical characterization of volcanic gas emissions at Santa Ana and San Miguel volcanoes, El Salvador, using remote-sensing and in situ measurements - Gutiérrez, Xochilt; Bobrowski, Nicole; Rüdiger, Julian; Liotta, Marcello; Geil, Bastien; Hoffmann, Thorsten; Gutiérrez, Eduardo; Dinger, Florian; Montalvo, Francisco; Villalobos, Mirian; Escobar, Demetrio (Frontiers in Earth Science, 2023)
Santa Ana and San Miguel are volcanoes along the Central American Volcanic Arc – CAVA, where the magmatism, basaltic to dacitic, is related to the near-orthogonal convergence of the Caribbean Plate and the subducting Cocos Plate. Both volcanoes are the most active ones in El Salvador with recent eruptive events in October 2005 (Santa Ana) and December 2013 (San Miguel). At each volcano, SO2 emissions are regularly monitored using ground-based scanning Differential Optical Absorption Spectrometer (Scan-DOAS) instruments that are part of the global "Network for Observation of Volcanic and Atmospheric Change" (NOVAC). We used the data series from these NOVAC stations in order to retrieve SO2 and minimum bromine emissions from Santa Ana and San Miguel volcanoes for the period 2006 – 2020 and 2008 – 2019, respectively. BrO was not detected above the detection limit. SO2 emission ranged from 10 to 7760 t/d, and from 10 to 5870 t/d for Santa Ana and San Miguel, respectively. In addition, the SO2 emissions are complemented with in-situ plume data collected during regular monitoring surveys (2018 – 2020) and two field campaigns in El Salvador (2019 and 2020). MultiGAS instruments recorded CO2, SO2, H2S and H2 concentrations. We determined an average CO2/SO2 ratio of 2.9 ± 0.6 when peak SO2 concentration exceeded 15 ppm at Santa Ana, while at San Miguel the CO2/SO2 ratio was 7.4 ± 1.8, but SO2 levels reached only up to 6.1 ppm. During the two field campaigns Raschig tubes (active alkaline trap) were used to collect plume samples which were analyzed with IC and ICP-MS to identify and quantify CO2, SO2, HCl, HF, and HBr. Additionally, also 1,3,5-trimethoxybenzene (TMB)-coated denuders were applied and subsequently analyzed by GC-MS to determine the sum of the reactive halogen species (Cl2, Br2, interhalogens, hypohalous acids). The RHS to sulfur ratios at Santa Ana and San Miguel lie in the range of 10-5.